ANALISIS KUALITAS PELAYANAN PEMBUATAN SERTIFIKAT TANAH DI KANTOR PERTANAHAN KABUPATEN KENDAL - Yoga Yuanitia Pratiwi; Hardi Warsono; Susi Sulandari (Journal of Public Policy and Management Review, 2013)
In government service quality is a very important factor and must be considered as a good quality service will give satisfaction to the community as a whole. Given as a servant of the state provide quality service is his their duty and obligation. However field data about the quality of service at the District Land Office Kendal indications of poor quality of services performed by employees, where people have to wait long amounts necessary to take care of the land titling and the accumulation of the completion certificate.. The purpose of this study was to describe the quality of service creation in the land certificate at the District Land Office Kendal.This research is a quantitative description of the five indicators that is tangible (direct evidence), reliability (reliability), responsiveness (responsiveness), acess (ease) and courtesy (employee attitudes). The sample in this study is that people who need land titling in Kendal District Land Office as much as 89 respondents. The collection of data by distributing questionnaires to a sample that comes to Kendal District Land Office to take care of the land certificate and contains closed questions with four choices answer. Then the research data is processed using the analysis of quantitative description using the mean (average).The results showed that the quality of service in the District Land Office Kendal included in category tangible (direct evidence), reliability (reliability), responsiveness (responsiveness) and courtesy (employee attitudes) all of them categorized as good and acess ( ease ) in enough categories.